Sleaze artists : cinema at the margins of taste, style, and politics - Sconce, Jeffrey, 1962- (E-Duke books scholarly collection., 2007)
Continuing film lovers' ongoing conversation about the low, the bad, and the sleazy face of cinema, 'Sleaze Artists' brings together film scholars with a shared interest in the questions posed by disreputable movies and suspect cinema.